Peramalan Nilai Saham BBCA Melalui Pendekatan Time Series Menggunakan Teknik Exponential Smoothing - Liantoni, Febri; Simanjuntak, Ondihon (JISKA (Jurnal Informatika Sunan Kalijaga), 2025)
Forecasting stock prices plays a crucial role in shaping investment strategies within the financial market. This article aims to predict the stock prices of Bank Central Asia (BBCA), a prominent entity in the Indonesian banking sector. Employing a time series methodology, this study utilizes the Exponential Smoothing technique to anticipate the fluctuations in BBCA's share prices. Meanwhile, the dataset used is the BBCA share price data from April 2001 to early January 2023. The final error rate in this forecast is 10%.